EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL DALAM PEMUNGUTAN PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN MIMIKA - Marthen Luther Rumboirusy; Darius Sabon Rain (CV. Adiba Aisha Amira, 2024)
This research aims to determine the effectiveness of using village income to support development in Kampung Kadun Jaya. The research method used in this research is descriptive research method. The data used is qualitative and quantitative data, which was collected using observation, interviews, documentation and questionnaires. To measure the effectiveness value in more detail, criteria based on Decree of the Minister of Home Affairs No. 690,900,327 of 1996 concerning Performance Appraisal Guidelines. The results of this research indicate that overall the implementation of the internal control system in collecting Land and Building Tax in the Rural and Urban Sector (PBB-P2) is ineffective with the effectiveness ratio still below 60%.